2016
DOI: 10.1097/j.pain.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Complexity, comorbidity, and health care costs associated with chronic widespread pain in primary care

Abstract: The objective was to estimate the prevalence of chronic widespread pain (CWP) and compare the quality-of-life (QoL), cardiovascular risk factors, comorbidity, complexity, and health costs with the reference population. A multicenter case-control study was conducted at 3 primary care centers in Barcelona between January and December 2012: 3048 randomized patients were evaluated for CWP according to the American College of Rheumatology definition. Questionnaires on pain, QoL, disability, fatigue, anxiety, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…Traumatic injuries, RA/OA, GI disorders, pulmonary disorders, CVD and/or CNS disorders were predictors of changes in pain intensity and spread of pain in the final models in this study (Tables II and III, model 2). These comorbidities have been related to CP intensity and spread (17,18,33,66) and change in intensity (45,67) and spread of pain (68,69). Previous studies found pulmonary diseases to be associated with pain intensity (19) and GI disorders, such as irritable bowel disease and spread of pain (70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic injuries, RA/OA, GI disorders, pulmonary disorders, CVD and/or CNS disorders were predictors of changes in pain intensity and spread of pain in the final models in this study (Tables II and III, model 2). These comorbidities have been related to CP intensity and spread (17,18,33,66) and change in intensity (45,67) and spread of pain (68,69). Previous studies found pulmonary diseases to be associated with pain intensity (19) and GI disorders, such as irritable bowel disease and spread of pain (70).…”
Section: Discussionmentioning
confidence: 99%
“…However, other comorbidities, e.g. heart disease, hypertension, diabetes and pulmonary disease, have also been as-sociated with CP (5,(17)(18)(19), and some of these are more frequent in widespread pain than in local pain (14). Moreover, some studies provide prediction models after adjustment for baseline pain (4,5,7), while others do not (6).…”
mentioning
confidence: 99%
“…Indeed, the reciprocal relationship between chronic pain and its comorbidities could be further investigated using longitudinal studies (Fishbain et al, 1997;Mossey and Gallagher, 2004;Tunks et al, 2008;Kroenke et al, 2011). It should be noted that in clinical situations, difficulties of relieving pain without eliminating its comorbidities have been increasingly recognized (Fishbain, 1999;Mcgrath and Dade, 2004;Ballantyne and Sullivan, 2015;Morales-Espinoza et al, 2015;Dale and Stacey, 2016).…”
Section: Psychophysiological Contributors Of Phnmentioning
confidence: 99%
“…Individuals experiencing CWP frequently experience additional clinical comorbidities such as irritable bowel syndrome, chronic fatigue syndrome, joint pain and headaches [3]. CWP is associated with poor quality of life [47] and many people are likely to be experiencing a mental health disorder such as depression, generalised anxiety disorder or panic attacks [8, 9]. In many cases complete relief from symptoms is unlikely but with appropriate treatment the impact upon quality of life, functioning and mental health symptoms can be significantly reduced.…”
Section: Introductionmentioning
confidence: 99%